Narratives as macroeconomic signals: Shaping expectations, confidence, and collective action - Christodoulou-Volos, Christos (Edelweiss Applied Science and Technology, 2025)
This paper reviews the emerging literature on how macroeconomic narratives—systematized, socially agreed-upon stories of the economy—function as signals that shape expectations, impact confidence, and drive collective economic behavior. Based on rational expectations, behavioral economics, signaling theory, narrative economics, and sociological methods, we examine how stories arise, disseminate through multiple channels, and gain strength through contagion and feedback loops. Empirical evidence demonstrates that policy communication stories, media framing, market commentaries, and public discourse can influence consumption, investment, asset prices, and political opinions individually. The literature’s primary shortcomings include vagueness of definitions, measurement problems, causality issues, and a lack of cross-cultural and non-crisis research. Future research directions involve conceptual standardization, richer narrative measurement, improved causal inference, channel attribution, and integration into macroeconomic models. The paper concludes with insights into the strategic potential of narrative management for policymakers, market participants, and media outlets, as well as associated risks in policy and practice.